Kebutuhan Banyaknya Titik Roof Outlet Pada Sistem Pemipaan - Fardhillah Adam Pratama; Fardhillah Adam (Cylinder : Jurnal Ilmiah Teknik Mesin, 2025)
The JST 01 Data Center development project is located on Jl. Bidara Cina in the Jatinegara District, East Jakarta, DKI Jakarta. The MT. Haryono Data Center stands at an elevation of 65 meters above sea level and comprises 14 floors, divided into two work areas: Gantry and IX. Rainfall at the JST 01 Data Center project site is recorded at 318.5 mm/h, based on data processed from BMKG Kemayoran, Cengkareng, and Pondok Betung stations. The analysis follows the Singapore Standard SS 525-2006 Code of Practice for Roof Drainage. The building's total roof area is 2,128.43 m², necessitating 14 Roof Outlet points for the operation of the Siphonic Rainwater System. Of these, five Roof Outlets are allocated to the Gantry area, while nine are distributed across the IX area.